Pengaruh Lingkungan Kerja, Kompensasi, dan Kepuasan Kerja terhadap Retensi Karyawan: Studi Sumber Daya Manusia pada Rajaklana Resort Yogyakarta - Sari, Vivin Kandita Permata; Jemadi, Jemadi (Universitas Proklamasi 45, 2024)
Employee retention is an important thing carried out by parties’ management to maintain the existence of employees so they continue to work within a company. The population in this study were employees of Rajaklana Resort in Yogyakarta. The sample used in this research was 47 people from a population selected using exhaustive sampling or saturated sampling/census techniques. This research was conducted using quantitative research methods. The information collection was carried out through distributing online surveys using the Google Form platform. This survey was addressed to 47 employees who work at Rajaklana Resort, an accommodation located in Yogyakarta. The research results show that the work environment and compensation have a positive and significant influence on employee retention, job satisfaction has no effect on employee retention. This indicates that employee retention is not influenced by job satisfaction.